Jean Piaget as a Pioneer of Modern Psychology: Critical Review - Bebane, Saeed Mohammed Noori Taher (Zanco Journal of Human Sciences, 2021)
There is increased interest in Jean Piaget contributions in modern psychology because his works focused on one of the most significant fields in human’s life. However, Piaget’s theory has been criticized due to shortcoming in methodology, ambiguity in his style, and characterizing human abilities negatively. This paper aimed to review some reasons that led researchers to criticize Piaget’s theory. Also, presenting some of his contributions in child development, which have led his theories to be considered as effective ones in modern psychology. This review suggested that majority of criticisms could be regarded to misunderstand of Piaget’s contributions, language barriers and his new methods in search. In addition, some of his contribution such as his theory of cognitive development and his contribution to characterize thinking of child with adult still regarded as an effective in modern psychology. Future research of Piaget is recommended to understand his purposes, subjects, and concepts from within.